Health and economic outcomes in the alumni of the Wounded Warrior Project, 2010-2012 - Krull, Heather; Oğuz, Mustafa, 1940- (Research report (Rand Corporation), 2014)
The Wounded Warrior Project (WWP) has developed programs to help care for injured service members and veterans. In order to assess the mental, physical, and economic health of its member population, as well as to gain an understanding of WWP participation, WWP is engaged in a five-year survey effort. The RAND Corporation was asked to analyze the first three survey waves in order to take a more in-depth look at survey responses to explore whether outcomes differ across various subsets of WWP's database of members and, where possible, compare the experiences and outcomes of alumni with those of other ill and injured populations. This report describes specifically how WWP alumni who responded to the surveys are faring in domains related to mental health and resiliency, physical health, and employment and finances. The study finds that WWP goals are being met across a wide range of outcomes of interest but that individuals who have never been married, who are male, who are employed, and who are in higher ranks enjoy better mental health outcomes. On the other hand, women and those in junior ranks report more favorably on their physical health. Finally, married respondents and officers are more likely to have higher levels of education, be employed, and own homes. These outcomes enable WWP to target its programming and messaging to the alumni in need of support in these areas.